Avaliação da resposta imune em doadores de sangue da cidade de Manaus infectados com o vírus da hepatite C (HCV) - (:unkn) unknown (Universidade Federal do Amazonas, 2007)
Hepatitis C virus represents a serious problem on public health, because or the high prevalence in the population, estimate from 0.3% to 14.5%. Hepatitis C is usually transmitted by blood and derivations, and the main etiologic agent of transfusion in the world. The chronic disease, with few clinical manifestations, occurs on 80% of the patients. Furthermore, the hepatitis C, is usually diagnosed when the individual is submitted to serological screening in blood banks. The specific laboratorial diagnostics of HCV is made on researching for anti-HCV antibodies, as on ELISA and Immunoblot tests, but a representative percentual of blood donors shows a specifics antibodies pattern against viral fractions that does not mean as a confirmed infection, but as a undetermined pattern. The immunological response profile developed by the individuals infected by HCV, involves responses of T helper cells 1, mediated by lymphocyte TCD4+ activation, as good as TCD8+ lymphocyte and IL-2 and IFN-production and seems to be an extremely important response for the viral clearance. The objective in the present study is analyze the immunological humoral and cellular response of blood donors whose sororeactive for hepatitis C in ELISA and Immunoblot tests. From September of 2005 to November of 2006 one hundred blood donors sororeactive to hepatitis C and one hundred healthy donors were invited to participate under their consentment of the study. In our results given by Immunoblot supplementary test, 46% showed undetermined results, 36% was reactive and 18% negative. Among negative samples 61.11% (n=11) had a weak positive reaction, among the undetermined, 76% (n=35) had DO/cut off rate below 2 and 50% (n=18) reactive had this rate above or equals to 3. There was no significative statistics differences observed among ALT data on both groups, thus remained under normal values. Among the activated lymphocytes population, those ones of LTCD3+/CD4+ showed statistics difference, whose the Immunoblot confirmed (HCV+/BLOT R) diagnose group shows a fewer cells number from the other groups (soronegative, HCV+/BLOT NR, HCV+/BLOT IND). Assessment the leukocyte subpopulation we can observe a significant statistics difference between CD69+neutrophiles and CD69+ monocytes, we did not observed significant difference between CD69+ lymphocyte population and CD69+ eosinophiles. We have conclude that the HCV infection persuade cellular changes that can be clearance viral or on chronic infection. However, to define this profile, there will be needed new researches.
Keywords: Hepatite C; Doadores de sangue; Resposta imune; Hepatitis C; Blood Donors; Immune Response; CIÊNCIAS DA SAÚDE